Solving the Puzzle: Molecular Research in Inflammatory Bowel Diseases - Krug, Susanne M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Inflammatory bowel disease (IBD) encompasses chronic idiopathic relapsing and remitting gastrointestinal autoimmune diseases characterized by chronic inflammatory disorders of complex etiology, posing clinical challenges due to their often therapy-refractory nature. The primary disorders within the IBD classification are ulcerative colitis (UC) and Crohn's disease (CD), sharing similarities but exhibiting distinct differences, sometimes making their discrimination challenging.A prominent feature of IBD is the inflammation of the intestinal mucosa, characterized by the robust and persistent infiltration of immune cells and compromised intestinal barrier integrity, leading to a phenomenon known as "leaky gut." Inflammation can manifest acutely or chronically, known as relapsing, and can increase in severity over time, thereby causing life-long morbidities and reduced quality of life for affected individuals, underscoring the need for a deeper comprehension of the molecular contributors to disease pathogenesis and progression.